Finite element analysis of shoulder rotator cuff - Phone, Myint Aung. (2010)
This final year project aims to create a feasible three-dimensional (3D) model of the human shoulder Rotator Cuff and its four tendons – Subscapularis, Supraspinatus, Infraspinatus and Teres Minor. The resulting computerized models are to be subsequently utilized for the Finite Element Analysis (FEA) – an attempt to simulate force, stress and strain distribution patterns that the human shoulder joint undergoes in different scenarios. The ultimate aim is to practically but virtually simulate the origination and consequences of muscular tears in the shoulder region which become a common problem in the aged people and in those subjected to repeated or excessive use.